Diagnosis of RET proto-oncogene in a family with a history Tamaulipas positive medullary thyroid cancer - Aguirre-Ezkauriatza, José (Universidad Autónoma de Tamaulipas, 2011)
In this paper we present the materials and the methodology used to search the mutation of codon 634 of exon 11 of RET Protooncogene of chromosome 10 in 11 persons, which 9 are relatives of a patient already diagnosed clinically and pathologically with medullary thyroid carcinoma, and this is the only case reported in the entire state of Tamaulipas. The mutation was found at codon 634 of exon 11 in positive patient, but not was found in the 9 relatives and in the negative. This concludes that if there is a close relationship between the molecular diagnosis and clinical diagnosis, as family members and the negative don´t present symptomatology of this disease, while positive patient clinically and pathologically diagnosed if present the mutation at codon 634.